SYNTACTIC STRUCTURES AND SEMANTIC DENOTATIONS OF GERUNDS IN BIOGRAPHICAL TEXTS - Wongkittiporn, Abhinan (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
Have you ever been asked who your role model is in your life? What did he/she do that impressed you? This study investigated how verbal gerunds are used in biographical texts in English. The study also investigated the linguistic perspectives on syntactic structures and semantic denotation. Previous research papers focused on the use of gerunds in English newspapers, literature, and international corpora. However, this study fills the gap by contributing to the view of biographical texts. As mentioned in previous studies, verbal gerunds denote factual events. It is intriguing to investigate whether these semantic denotations are applied to biographical texts, where the genre of writing has a mixture of narrative writing and a history of someone’s life. The materials in this study are the biographical texts of Queen Elizabeth II, the late Prince Philip, Duke of Edinburgh, and the late Princess Dianna, since they are the best-sellers (amazon.com). The study includes 41 sentences extracted from the material, containing a total of 300,000 words. The data validation follows the Index of Item Objective Congruence (IOC), where three experts, being English instructors, were asked to validate the data analysis. The results of this study show that the use of gerunds is explained by various linguistic perspectives. Syntactically, the use of gerunds is equivalent to the DP subject, which is coreferential with a higher clause (Radford, 2009). The semantic denotations of gerunds in biographical texts indicate simultaneous events. It is hoped that this study will be beneficial for learners of English as a Second Language (ESL) and English as a Foreign Language (EFL) to write biographical texts systematically and interestingly.